Examining the Role of Women’s Labor Participation in CO2 Emissions in Saudi Arabia - Mahmood, Haider; Tanveer, Muhammad (International Journal of Energy Economics and Policy, 2024)
Women can play an active role in determining environmental quality, and Saudi women’s share in the labor market is increasing considerably. Women's participation is still low in the labor market, and their participation might affect the aggregated environmental situation. Therefore, we explore the effect of Women's Labor Participation (WLP) on CO2 emissions in Saudi Arabia from 1990 to 2022 by employing a cointegration technique. The Environmental Kuznets Curve (EKC) is tested and substantiated in the long run, but it is not verified in the short run. WLP raises CO2 emissions. Thus, women's labor market entry has environmental consequences. Moreover, trade openness also contributes to CO2 emissions over a long period of time. Nevertheless, its short-term impact is environmentally pleasant. The study recommends checking environmental problems out of WLP by developing gender-responsive environmental policies. So, gender equality and sustainable growth would be targeted simultaneously.